1979
DOI: 10.1115/1.3448721
|View full text |Cite
|
Sign up to set email alerts
|

Free Shear Layer Behavior in Rotating Systems

Abstract: Experiments are reported concerning turbulent separated flow downstream of a backward-facing step in a two-dimensional channel that was rotated at a steady rate about a spanwise axis. Reattachment distance is reported as a function of Reynolds number, rotation direction and number and passage aspect ratio. Extensive flow visualization films have been produced. It is demonstrated that turbulent motions in a free shear layer may be suppressed or enhanced by system rotation according to the sense of the rotation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…These investigators have documented strong secondary flows and have identified aspects of flow stability which produce streamwise oriented, vortex-like structures in the flow of rotating radial passages. The effects of rotation on the location of flow reattachment after a backward facing step was presented by Rothe and Johnston (1979). This work was especially helpful in understanding the effects of rotation on heat transfer in passages with normal trips.…”
Section: Previous Studiesmentioning
confidence: 99%
“…These investigators have documented strong secondary flows and have identified aspects of flow stability which produce streamwise oriented, vortex-like structures in the flow of rotating radial passages. The effects of rotation on the location of flow reattachment after a backward facing step was presented by Rothe and Johnston (1979). This work was especially helpful in understanding the effects of rotation on heat transfer in passages with normal trips.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In an earlier study, Rohte and Johnston [1979] experimentally demonstrated that the turbulent shear layer past a backstep for low blockage ratio is more affected under stabilizing rotation (leading side of radially outward flow) than destabilizing rotation (trailing side of radially outward flow). The changes in the first-pass leading and trailing sides are similar to a smooth channel (Han et Beside the Coriolis force in heated rotating ducts, the centrifugal force induces buoyancy effects that can play a major role in the heat transfer patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Incompressible flows in rotating fields have been extensively studied by a number of researches [6][7][8][9] to understand air currents in the atmosphere and to grasp turbomachinery flows. Turbulent flows in channel rotating around the spanwise axis were investigated by the LES [10,11] and the DNS [12,13], and the effects of the Coriolis force on the flow stability and turbulent structures were explored.…”
Section: Introductionmentioning
confidence: 99%